STRATEGI MITIGASI RESIKO KERUSAKAN ARSIP FISIK DI PT. JASAMARGA SOLO NGAWI - Nurrohmah Aldiena Syafitri; Herwati Dwi Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical archives are maintained as evidence of daily office operational activities and therefore play an important role. However, physical archives at PT Jasamarga Solo Ngawi are vulnerable to damage, making risk mitigation efforts necessary to prevent archive deterioration. This study employed a descriptive qualitative method, with data collected through direct observation, interviews, and documentation. The research discusses the condition of physical archives, the factors causing archive damage, and the mitigation strategies implemented at PT Jasamarga Solo Ngawi. The results revealed that several archives had turned yellow, become moldy, torn, shredded, and contained writing that was difficult to read. These damages were caused by internal factors such as paper quality, glue, and ink, as well as external factors including environmental conditions, biological agents, human factors, and potential natural disasters. The findings indicate that PT Jasamarga Solo Ngawi has not yet implemented optimal mitigation strategies for physical archive preservation. Considering the importance of archival documents, proper archive management is required, including archive arrangement based on classification systems, improvement of facilities and disaster protection equipment in archive storage rooms, and the presence of competent archivists to manage archives from creation to disposal in accordance with national archival standards. These efforts are necessary to ensure that archival data and information remain intact, easily accessible when needed, and reliable as references.